2021
DOI: 10.1177/1420326x211030786
|View full text |Cite
|
Sign up to set email alerts
|

Energy agenda of architectural formation: To progress sustainable built environment through the approach of energy-driven architectural formation

Abstract: Until now, the significance of environmental regulation for disciplinary autonomy of architecture is still being underestimated. 1,2 Reyner Banham 3 wrote in the very beginning of his literal works 'The Architecture of the Well-tempered Environment':In a world more humanely disposed, and more conscious of where the prime human responsibilities of architects lie, the chapters that follow would need no apology, and probably never need to be written.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For a large number of buildings, data mining algorithms can be employed to analyze low-carbon design and operational strategies from a macro perspective. For example, Zhang Zhang et al [9] used data mining techniques to analyze many office buildings, identifying more carbon-efficient design strategies, such as lower carbon emissions in buildings with centralized heating. The prerequisite for using data mining techniques is the collection of extensive data on building design and operations, which limits the widespread application of this technology.…”
Section: Carbon Emission Calculation Methods During Operational Phasementioning
confidence: 99%
“…For a large number of buildings, data mining algorithms can be employed to analyze low-carbon design and operational strategies from a macro perspective. For example, Zhang Zhang et al [9] used data mining techniques to analyze many office buildings, identifying more carbon-efficient design strategies, such as lower carbon emissions in buildings with centralized heating. The prerequisite for using data mining techniques is the collection of extensive data on building design and operations, which limits the widespread application of this technology.…”
Section: Carbon Emission Calculation Methods During Operational Phasementioning
confidence: 99%
“…It is known that innovative materials, recycled, bio-based materials can be preferred in facade construction, as well as natural, carbon-storing, conventional, and industrialized materials such as wood can reduce environmental impacts [20]. Zang et al [21] emphasize that the structures must be built with appropriate forms that respond to the local climate and meet the criterion for comfort. Prefabricated facade panels, which are prefabricated products, are components that can help reduce operational energy use.…”
Section: Introductionmentioning
confidence: 99%
“…10 Therefore, it is imperative for developing countries to seriously consider assessing and controlling greenhouse emissions and energy consumption to avoid future disasters. 11 Research demonstrated that energy consumption by buildings has a significant effect on climate change. 12,13 In this respect, energy preservation approaches have had a positive role in reducing air pollution and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…10 Therefore, it is imperative for developing countries to seriously consider assessing and controlling greenhouse emissions and energy consumption to avoid future disasters. 11…”
Section: Introductionmentioning
confidence: 99%